Investigation of errors in the representation of 3D models in determining the parameters of parts of devices BY the example of a two-mass rotating system with elastic coupling - S. A. Bratchikov; E. A. Abramova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The objective of the study is to consider the application field of modern device development and design methods using the means of 3D modeling and simulation of physical processes. The validity of the application and criteria for the reliability of the results obtained in the sequential design of the mechanical part of the electric drive and the control system are investigated.Methods. Methods of model representation of 3D objects in computer-aided design systems are considered, as well as methods for solving problems of determining strain under the applied load. Using the example of an elementary joint, the obtained results of the dynamic characteristic of an elastic shaft in a computer-aided design system are compared with those calculated analytically.Results. The article defines the basic principles and relations applicable to describing the shape of 3D models. Methods are shown by which it is possible to obtain information about the mass-centering model characteristics. The relations that form the basis of numerical methods for solving problems of determining elastic deformations of bodies are also given. The error that can occur when using insufficiently small elementary volumes in solving the problem of determining elastic deformation is shown.Conclusion. The use of 3D modeling in the design of complex technical systems is justified and speeds up production processes. However, numerical methods cannot always give an accurate result leading to the need to either increase the complexity of calculations or additionally adjust some designed device parameters.